The Impact of Macroeconomic Variables on Stock Prices: An Empirical Analysis of Karachi Stock Exchange - Hussain, Muhammad Mubashir; Aamir, Muhammad; Rasool, Nosheen; Fayyaz, Maleeha; Mumtaz, Maryam (Mediterranean Journal of Social Sciences, 2012)
The intention of this study was to investigate the causal relationship, both long-run and short-run, between KSE (Karachi StockExchange) and some macroeconomic variables in Pakistan. The monthly data of all macroeconomic variables and stock prices wastaken from January 2001 to December 2010. In this paper, the variables which have not been previously studied by the researchers inPakistan were also included. The set of macroeconomic variables used in this study as an independent variables were Exchange Rate(ER), Foreign Exchange Reserves (FER), Industrial Production Index (IPI), Interest Rate (IR), Imports (M), Money Supply (MS),Wholesale Price Index (WPI) and Exports (X). The stock price index of KSE, which is the largest stock exchange of Pakistan, was takenas a dependent variable. The statistical techniques, which were employed in this study, include the Augmented Dickey-Fuller (ADF) andKwiatkowski-Phillips-Schmidt-Shin (KPSS) unit root test, Johansen Co-integration test, Vector Error Correction Model (VECM) andGranger Causality test. The study revealed the presence of long-run association between macroeconomics variables and stock prices.FER, IR, M, MS and WPI showed a positive and significant relationship with stock prices, while ER and X indicated a negative andinsignificant impact on stock prices but IPI has a negative but significant relationship with stock prices. The two error correction terms likeVecm1 (-1) and Vecm2 (-1) were resulted from VECM, the first error correction term was significant and indicated short term adjustmentstowards the equilibrium path. The results of Granger Causality showed that MS and WPI have bi-directional relation while ER, FER andM have uni-directional relationship with the stock prices but IPI, IR and X showed not any casual relationship.